The Borgiani Armeni 65 Manuscript A Witness to Early Modern Armenian Religious-Economic Diasporic Connectivity Between Aleppo, Jerusalem and Beyond - Ghazaryan Diana (PÁZMÁNY PAPERS, 2025)
The manuscript Borgiani armeni 65 from the collection of Vatican Apostolic Library is one of the 137 Armenian documents preserved there. The document is rare in its kind as it contains different pages from different time periods of Armenian history bound together. The page 8r of it is a unique letter written in 1711 in the monastery of Saint James – the Armenian Patriarchate of Jerusalem. Besides being an invaluable source for historical analysis, it can also be perceived as a representation of early modern connectivity among Armenian churches in the Ottoman Empire. In this case, the letter is an alms-collecting request to the Armenian Diocese of Beroea (Aleppo). Besides being considered a tool of early modern connectivity and mobility, the performative turn in the requesting part of the letter allows it to be analyzed from a unique angle.